The effects of pargyline on overflow of transmitter and uptake of noradrenaline in the cat spleen - Blakeley, A. G. H. (1973)
1. Twenty minutes after the addition of pargyline (5 × 10(-4)M) to blood perfusing the isolated spleen of the cat, the overflow of transmitter resulting from stimulation of the sympathetic nerves increased 2·3-3-fold. Lower doses of pargyline did not significantly affect overflow. 2. Monoamine oxidase activity, measured with either radioactively labelled tyramine or noradrenaline as substrate, was almost completely inhibited by doses of pargyline in the range of 10(-4)M to 5 × 10(-4)M. Inhibition of enzyme activity was not correlated with the effect on overflow. Pargyline had only a slight inhibitory effect on catechol-O-methyl transferase. 3. Uptake of a 1 μg injection (pulse) of labelled noradrenaline, following pargyline (5 × 10(-4)M), was increased to 199·1% of that found in control experiments. 4. Pargyline significantly reduced the vascular responses to nerve stimulation but had no significant effect on capsular responses. 5. The inhibitor had no effect on resting overflow of labelled noradrenaline from the spleen but doubled the overflow of labelled noradrenaline following nerve stimulation. 6. It is suggested that the effect of pargyline on overflow is due to increased release of transmitter during nerve stimulation. 7. The possible clinical significance of these findings is discussed.